2016
DOI: 10.14581/jer.16015
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Daytime Sleepiness and Sleep Disorders in a Population of Patients with Epilepsy: a Case-Control Study

Abstract: Background and PurposeThere are several primary causes for excessive daytime sleepiness (EDS) and sleep disorders in patients with epilepsy. Up to now, studies in the literature report conflicting data in terms of both prevalence and aetiology. The aim of our study was therefore to evaluate the prevalence of EDS and some sleep disorders in a population of patients with epilepsy treated with no more than two antiepileptic drugs (AEDs). We also investigated the role of the depression of mood as a variable that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…40 Many other studies have found high rates of EDS, sleep fragmentation, and disturbed sleep architecture in focal epilepsy, as well as increased risk of obstructive sleep apnea. [41][42][43] Furthermore, several investigations have found that EDS and sleep disturbances are not solely related to antiepileptic medications, [44][45][46] but instead are closely associated with severity and/or duration of disease, [45][46][47] and may be accompanied by decline in quality of life. 44,48 Overall, these clinical studies suggest potential impairment of vigilance networks in focal epilepsy patients.…”
Section: Demonstrating Impaired Vigilance In Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…40 Many other studies have found high rates of EDS, sleep fragmentation, and disturbed sleep architecture in focal epilepsy, as well as increased risk of obstructive sleep apnea. [41][42][43] Furthermore, several investigations have found that EDS and sleep disturbances are not solely related to antiepileptic medications, [44][45][46] but instead are closely associated with severity and/or duration of disease, [45][46][47] and may be accompanied by decline in quality of life. 44,48 Overall, these clinical studies suggest potential impairment of vigilance networks in focal epilepsy patients.…”
Section: Demonstrating Impaired Vigilance In Epilepsymentioning
confidence: 99%
“…In one recent neuroimaging study of mTLE patients after epilepsy surgery, we noted that certain functional connectivity alternations recovered to levels resembling those of controls in patients who became free of seizures, regardless of whether they were still taking medications. 99 Furthermore, several studies have noted impaired vigilance, 26,39 neurocognitive deficits, 24,37,38 and EDS [44][45][46] in epilepsy patients that are not fully explained by medications and often present in the absence of medications. Therefore, distinguishing the contributions of medications and subcortical network impairments to vigilance and cognition is critical to understand their clinical implications in mTLE treatment.…”
Section: Effects Of Medicationsmentioning
confidence: 99%
“…Consequently, it is not surprising that apathy is closely related to depression. Furthermore, depressed PWE have been reported to elicit comorbid anxiety and sleep problems [11,33,34]. Thus, it is natural that apathy is likely to accompany these psychosomatic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive daytime sleepiness is a common complaint in patients with epilepsy (PWE). Evidence suggests that uncontrolled seizures, comorbid sleep disorders, and mood disorders are major contributing factors [11,14,28,49]. There are conflicting studies regarding the impact of AEDs on daytime sleepiness.…”
Section: Hypersomnia and Narcolepsymentioning
confidence: 99%
“…A recent study by Maestri et al demonstrated that newly diagnosed PWE not on AEDs had no difference from controls on Multiple Sleep Latency tests, reaction times, or Epworth Sleepiness Scale scores [26]. Another study demonstrated 11.1% of PWE had excessive daytime sleepiness, more frequently in the presence of obstructive sleep apnea and depression [49]. Although excessive daytime sleepiness is frequently reported, comorbid narcolepsy and epilepsy has been infrequently documented with only a few recent case series published [50,51].…”
Section: Hypersomnia and Narcolepsymentioning
confidence: 99%